IMPLEMENTASI PASAL 55 UNDANG-UNDANG NOMOR 6 TAHUN 2014 TERHADAP KEBIJAKAN ALOKASI DANA DESA DI WILAYAH KECAMATAN KARANG TINGGI BENGKULU TENGAH - Kresnawati Kresnawati; Jamil Afrianto (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2020)
The Village Fund Allocation (ADD) sourced from the APBN which is intended for villages that is transferred through the Regency / City APBD and is used to finance governance, development implementation, community development, and community empowerment in the village. Article 55 of Law Number 6 Year 2014 concerning Villages, said that the Village Consultative Body (BPD) has the function of accommodating and channeling the aspirations of the village community, discussing and agreeing on a Village Regulation Draft with the Village Head, and the BPD has the authority to supervise the performance of the Village Head so that fraud does not occur.This type of research is quantitative that aims to conduct desk monitoring Implementation of Article 55 of Law number 6 of 2014 concerning the function of the village consultative body against the Village Fund Allocation Policy in the Karang Tinggigi District of Central Bengkulu Regency. The research data was obtained by distributing questionnaires in 18 (eighteen) villages of Karang Tinggi District, Central Bengkulu District who were serving as Village Officials and the Village Consultative Body. The analytical method used is linear regression using statistical software, the target outputs of this research are published in national journals and held in a national seminar so that it can be implemented directly by the village consultative body in carrying out its functions.The results of this study prove that there is a significant influence between the implementation of article 55 of Law N0. 6 of 2014 from the legislative function and aspirations towards village fund allocation policies.Â Keywords: Implementation of article 55 of the Village Law, Village Fund Allocation Policy